Phylogenetic relationships of living and fossil African papionins: Combined evidence from morphology and molecules. Issue 123 (October 2018) - Pugh, Kelsey D.; Gilbert, Christopher C.
Abstract: African papionins are a highly successful subtribe of Old World monkeys with an extensive fossil record. On the basis of both molecular and morphological data, crown African papionins are divided into two clades: Cercocebus/Mandrillus and Papio/Lophocebus/Rungwecebus/Theropithecus (P/L/R/T), though phylogenetic relationships in the latter clade, among both fossil and extant taxa, remain difficult to resolve. While previous phylogenetic studies have focused on either molecular or morphological data, here African papionin molecular and morphological data were combined using both supermatrix and molecular backbone approaches. Theropithecus is supported as the sister taxon to Papio/Lophocebus/Rungwecebus, and while supermatrix analyses using Bayesian methods are largely unresolved, analyses using parsimony are broadly similar to earlier studies. Thus, the position of Rungwecebus relative to Papio and Lophocebus remains equivocal, possibly due to complex patterns of reticulation. Parapapio is likely a paraphyletic grouping of primitive African papionins or possibly a collection of stem P/L/R/T taxa, and a similar phylogenetic position is also hypothesized for Pliopapio . ?Papio izodi is either a stem or crown P/L/R/T taxon, but does not group with other Papio taxa. Dinopithecus and Gorgopithecus are also stem or crown P/L/R/T taxa, but their phylogenetic positions remain unstable. Finally, T. baringensis is likely the most basal Theropithecus taxon, with T. gelada and T. oswaldi sister taxa to the exclusion of T. brumpti . By integrating large amounts of molecular and morphological data, combined with the application of updated parsimony and Bayesian methods, this study represents the most comprehensive analysis of African papionin phylogenetic history to date.